The frisson of No-Touch: A Fan's Gallant Allegory of the Senses. (June 2014) - Cherbuliez, Juliette
Abstract : The double-sided Allegory of the Senses, shows, on one side, a late- seventeenth-century courtly depiction of hearing, sight, and smell. It is possible to read these as three vignettes depicting gallant sociability in elite society: the very sociability in which the fan played a crucial role. Our interpretation must change, however, if we acknowledge both the 'missing' senses of taste and touch not directly depicted on the fan, and the fan's reverse, a rural scene of a couple. The play of absent and present senses, and the tension between the courtly vignettes of the primary image and its humbler other side, suggest also a possible 'fluttering' of signification, not unlike the motion of a fan itself, which may undo some of the gallant visual rhetoric which at first glance appears to dominate an understanding of this fan.